Addressing the Problem of Political Vigilantism in Ghana through the Conceptual Lens of Wicked Problems - Asamoah, K. (Journal of Asian and African Studies, 2019)
Ghana entered into the Fourth Republic in 1993 after experiencing political instability over two decades. A defining feature that has characterized the Fourth Republic of Ghana and marred Ghana’s democratic credentials is the emergence of political vigilantism. Political vigilantism has basically been perpetuated by the two leading political parties in Ghana: the New Patriotic Party and the National Democratic Party. The major political actors in the political system of Ghana continue to express the debilitating effects of political vigilantism on Ghana’s democratic advancement, nevertheless, it continues to persist in monumental proportion in our political dispensation. Using a qualitative research approach, the paper examines the factors responsible for the pervasiveness of political vigilantism under the Fourth Republic of Ghana and proffer some plausible solutions to address this political canker.
Research Article
Keywords: Ghana; Africa; political; vigilantism; wicked problem; democratic